PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PENIPUAN DI WILAYAH KOTA TEMBILAHAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Irdan Hasan; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
One form of crime that is still very common in society is fraud. For the unscrupulous, the crime is not so difficult to do. Fraud can be done simply by using good communication skills so that someone can convince others. Crimes in the form of fraud and embezzlement are threatened with criminal sanctions, the enforcement still lacks a deterrent effect on violations, because in criminal law enforcement it is not only sufficient to regulate an act regulated in the law, but it also requires the law enforcement agencies to implement the provisions of the lawThis type of research can be classified in the type of sociological (empirical) legal research, because in this study the authors directly conduct research at the location or place of study in order to provide a complete and clear picture of the problem under study. This research was conducted in the Tembilahan City Region of Indragiri Hilir Regency, Riau Province. The population and sample are the head of the police criminal detective unit in Tembilahan, the Tembilahan police auxiliary investigator, the Chairman of the Tembilahan District Court, Perpetrators of fraud and Victims of fraud. Data sources used are primary data and secondary data.The conclusion that can be obtained from the results of the study is the enforcement of criminal law against fraud in the Tembilahan City Region, Indragiri Hilir Regency, Riau Province, which is still not going well and there are still many frauds that occur. Fraud criminal acts that occur today can be done in various ways from simple to complex. The panel of judges who handed down the conviction verdict referred to the facts of the trial. So that some of the victims were disappointed and judged unfairly against the verdict handed down. The obstacles experienced by criminal law enforcement against fraud in the Tembilahan City Region of Indragiri Hilir Regency, Riau Province consist of law enforcement officers, legal factors and community factors. The factor of law enforcement officers is professional and understanding of fraud that has undergone development. The legal factor is difficult in terms of proof if law enforcement officers are only guided by articles in the Criminal Code. and community factors, namely the community does not fully know and understand various modes of crime, one of which is fraud. Community understanding and knowledge related to the existence of various modes of crime, one of which is fraud.Keywords: Law Enforcement, Criminal Acts, Fraud